The Influence of the Problem Based Learning Model on Students’ Critical Thinking Ability and Learning Motivation in Mathematics Learning - Mayshe Baidannur Siregar; Suci Dahlya Narpila (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2023)
This study aims to determine the effect of the problem based learning (PBL) learning model on critical thinking skills and students' motivation in learning mathematics. This type of research is a quasi experiment (quasi experiment). The design model uses a pretest posttest control group design. The population of this study was all students of class VII SMP Kesatria Medan in the 2023/2024 academic year consisting of 30 students. Sampling was carried out using random sampling technique and the research sample was obtained, namely VII-1 totaling 16 students as the control class and 14 students VII-2 as the experimental class. The research instrument used tests in the form of essays. Data analysis techniques used descriptive analysis which included normality tests, homogeneity tests and hypothesis tests, namely the t-test (paired sample t-test). The results of the study show the sig. (2-tailed) of 0.000 <0.05, it can be concluded that students who get the problem-based learning model are better than students who use conventional learning models